Enhancing Critical Thinking: Teacher's Perspective on Problem-Based Learning Using Flipbook - Fitriana, Eka; Djono, Djono; Sumaryati, Sri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The research aimed to analyze utilizing a problem-based learning flipbook of accounting in vocational high schools related to students' critical thinking abilities viewed from the teacher's perspective regarding the learning needs and find out obstacles factors to learning to account This research uses mixed research methods, namely qualitative and quantitative designs The research subjects were 12 accounting teachers at Tulungagung Regency Vocational Schools The sampling technique uses simple random sampling Quantitative data was collected from 12 accounting teachers Data analysis uses Miles and Huberman's interactive analysis method, consisting of data collection (observation, interviews, document analysis), condensation, data presentation (data display) and conclusions The research results show that accounting learning has many obstacles in schools, namely not empowering students' critical thinking abilities; learning strategies are less varied, and the use of open digital media/materials is not optimal, so teachers need an understanding of the importance of innovative teaching strategies and media learning, such as problem-based learning-flipbook in enhancing critical thinking for vocational high school students.